(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Bitumen is often used in the building of flexible pavements in the capacity of a binder. In the current investigation, it is suggested that the characteristics of bitumen might be improved by modifying it with EVA polymer. The useful life of pavements may be shortened as a consequence of rutting. In the event that the rutting depth is very severe, water may pool in the pavement area, which may cause vehicles to hydroplane. The results of a bending beam rheometer test (BBR) for creep stiffness at lower temperatures indicate that the creep stiffness of modified bitumen was lowered, while the m value was enhanced. The in-situ polymer modified binders that were produced demonstrated significantly reduced stiffness and satisfied the required parameters up to a temperature of -18 degrees Celsius.